(untitled) (Revista Rupturas, 2018)
As happened in the last general elections in Costa Rica, Christian parties are emerging throughout Latin America, especially neo-Pentecostals, presenting themselves as defenders and, therefore possessors, of truths and values that they see in danger: conception of life, sexuality, human couple, etc. And it is common, even in secular media, to recognize them some competence. In this regard, the question has to be asked academically, and the present work does: do religions really have specific truths about it? And the answer is negative. In the past, under a mythical epistemology, they believed they were competent and they were. Today, under a critical epistemology, they are no longer so. Its truths and values are those of the anthropologies they assume: ethics and philosophies often already expired, without epistemological validity. Definitely, the pretension of the churches has to be submitted to debate.